O papel da cooperação para a inovação: uma análise da contribuição nacional e estrangeira na indústria de transformação brasileira no período de 1998 a 2014 - Ferreira, Marciel Aparecido (2018)
Innovation, regarded as a means for maintaining the firm's competitiveness, has become more complex, costly and risky. In addition, it has led to an increase in the number of cooperative relations over the past few years. Thus, the present study aimed to identify the role of cooperation for innovation in Brazilian manufacturing industries from 1998 to 2014. In particular, the study utilized secondary data from three databases, especially PINTEC, aiming at identifying determinants of cooperation and innovation, as well as the impact of sources of information of national and foreign origin on them. In order to achieve these goals, the study was based on theories of Industrial Organization and analyzed through a model of instrumental variables in two stages. The results pointed out the companies that have the cooperation as the main responsible for the development of products; companies that have a research and development (R & D) sector; patents deposited in the year; companies in high-level technology sector; and companies in the industry that received government funding to innovate; are factors that have had a positive impact on the number of innovations since, before that, there is a relationship of cooperation, whereas, the acquisition impacts, in one of the analyzes, in a negative and not significant way in another. It has also been found that innovation acquisitions and firms with cooperative relationships, along with government support, also have a positive influence on the number of firms implementing innovations. Finally, as far as the analysis of information sources is concerned, the source of international information was not significant neither for cooperation for innovation nor for innovation, while the source of national information was significant and positive for the first case and significant and negative for the second. It is concluded that, in cooperating, a greater number of factors are considered significant in terms of the number of firms innovating, allowing to conclude that cooperation optimizes these resources while, in the absence of cooperation, the way to innovate is to acquire or seek governmental support. In addition, national information contributes to the generation of a greater number of innovating firms, provided that the firm cooperates first.